Postoperative ileus: Recent developments in pathophysiology and management. Issue 3 (June 2015) - Bragg, Damian; El-Sharkawy, Ahmed M.; Psaltis, Emmanouil; Maxwell-Armstrong, Charles A.; Lobo, Dileep N.
Summary Background & aims Postoperative ileus (POI) is a frequent occurrence after abdominal and other types of surgery, and is associated with significant morbidity and costs to health care providers. The aims of this narrative review were to provide an update of classification systems, preventive techniques, pathophysiological mechanisms, and treatment options for established POI. Methods The Web of Science, MEDLINE, PubMed and Google Scholar databases were searched using the key phrases 'ileus', 'postoperative ileus' and 'definition', for relevant studies published in English from January 1997 to August 2014. Results POI is still a problematic and frequent complication of surgery. Fluid overload, exogenous opioids, neurohormonal dysfunction, and gastrointestinal stretch and inflammation are key mechanisms in the pathophysiology of POI. Evidence is supportive of thoracic epidural analgesia, avoidance of salt and water overload, alvimopan and gum chewing as measures for the prevention of POI, and should be incorporated into perioperative care protocols. Minimal access surgery and avoidance of nasogastric tubes may also help. Novel strategies are emerging, but further studies are required for the treatment of prolonged POI, where evidence is still lacking. Conclusions Although POI is often inevitable, methods to reduce its duration and facilitate recovery of postoperative gastrointestinal function are evolving rapidly. Utilisation of standardised diagnostic classification systems will help improve applicability of future studies.